Reducing Electromagnetic Radiation Around the Fourth Generation Base Stations - Christopher C. NWAOGU; Nnamdi AHUCHAOGU (FUDMA Journal of Engineering and Technology, 2026)
Electromagnetic radiations and interferences, poses health hazards both to man and his environment the importance of reducing it cannot be over emphasized. This work focused on the reduction of electromagnetic interference (EMI) around 4G base station using filter techniques. The projected rise in wireless communication network generations and the inherent electromagnetic emission that come along with the technologies have necessitated the search for better ways of reducing the electromagnetic interference. Considering the current electromagnetic interference concerns, the base station is the hub of the electromagnetic interference. This research examined different ways of deploying the finite impulse response filters (FIR) at the base station level to help reduce the impact of EMI around the 4G base stations. The research adopted the finite impulse response (FIR) filter technique, which is connected at the transceiver point at the base station level. The data used for analysis in the developed model were extracted from the daily collection of data from the service provider operators. Electromagnetic interference (EMI) for the filtered and unfiltered base stations were analyzed using the International Commission on Non-Ionizing Radiation Protection (ICNIRP) model. Data for five 4G base station within the Umuahia metropolis were used. The results obtained for 4G base stations showed that the deployment of Filter reduced the electromagnetic power density around a 4G base station. As without the filters the power densities were 3.755, 2.708, 1.280, 0.681, 0.412, 0.273, 0.193, 0.144, 0.111, 0.088 and 0.072. On the deployment of the FIR filters the power densities were reduced to 3.552, 2.562, 1.211, 0.645, 0.390, 0.258, 0.183, 0.105, 0.083 and 0.068 respectively.
Keywords: Electric field strength, Magnetic Field strength, Power density, electromagnetic radiation, filters.